Probabilistic linkage in household survey on hospital care usage Relacionamento probabilístico em inquérito domiciliar sobre uso de serviços hospitalares - Cláudia Medina Coeli; Régis Blais; Maria do Carmo Esteves da Costa; Liz Maria de Almeida (Universidade de São Paulo, 2003)
OBJECTIVE: To evaluate the potential advantages and limitations of the use of the Brazilian hospital admission authorization forms database and the probabilistic record linkage methodology for the validation of reported utilization of hospital care services in household surveys. METHODS: A total of 2,288 households interviews were conducted in the county of Duque de Caxias, Brazil. Information on the occurrence of at least one hospital admission in the year preceding the interview was obtained from a total of 10,733 household members. The 130 records of household members who reported at least one hospital admission in a public hospital were linked to a hospital database with 801,587 records, using an automatic probabilistic approach combined with an extensive clerical review. RESULTS: Seventy-four (57%) of the 130 household members were identified in the hospital database. Yet only 60 subjects (46%) showed a record of hospitalization in the hospital database in the study period. Hospital admissions due to a surgery procedure were significantly more likely to have been identified in the hospital database. The low level of concordance seen in the study can be explained by the following factors: errors in the linkage process; a telescoping effect; and an incomplete record in the hospital database. CONCLUSIONS: The use of hospital administrative databases and probabilistic linkage methodology may represent a methodological alternative for the validation of reported utilization of health care services, but some strategies should be employed in order to minimize the problems related to the use of this methodology in non-ideal conditions. Ideally, a single identifier, such as a personal health insurance number, and the universal coverage of the database would be desirable. OBJETIVO: Avaliar as potenciais vantagens e limitações do uso das bases de dados dos formulários de Autorização de Internação Hospitalar e da metodologia do relacionamento probabilístico de registros, para a validação de relatos de utilização de serviços hospitalares durante inquéritos domiciliares. MÉTODOS: Um total de 2.288 entrevistas domiciliares foram realizadas em Duque de Caxias, RJ (Brasil). A informação sobre a ocorrência de ao menos uma hospitalização durante o ano que precedeu a entrevista foi obtida de um total de 10.733 moradores. Os 130 registros de moradores que relataram ao menos uma hospitalização em hospital público foram relacionadas com uma base de dados hospitalares contendo 801.587 registros, usando um processo automático combinado com uma extensiva revisão manual. RESULTADOS: Dos 130 moradores, foram encontrados registros de 74 (57%) na base hospitalar. Entretanto, somente 60 indivíduos (46%) estiveram hospitalizados na base hospitalar dentro do período de referência do estudo. Hospitalizações devido a procedimentos cirúrgicos foram significativamente mais prováveis de serem identificadas na base hospitalar. O baixo nível de concordância obtido no estudo pode ser explicado pelos seguintes fatores: erros no processo de relacionamento, efeito telescópio e um registro incompleto dos episódios na base hospitalar. CONCLUSÕES: O uso de bases hospitalares administrativas e da metodologia de relacionamento probabilístico de registros pode representar uma alternativa metodológica para validação de relatos de utilização de serviços de cuidados de saúde. Entretanto, algumas estratégias devem ser empregadas com o objetivo de minimizar os problemas relacionados ao uso dessa metodologia em condições não ideais. Um identificador unívoco, como o número de seguro saúde e a cobertura universal do banco de dados, seria desejado.